IMPROVING STUDENT LEARNING OUTCOMES IN THE IV GRADE OF SCIENCE USING EXPERIMENTAL METHODS - Dewi Setiawati; Nurul Kamila Sari; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
The research based on the fact at 104 Langensari-Senanggalih Elementary school, is found the problem is learning outcome is low in the natural science subject. Therefore, was research with the aim to improve students activity and learning outcome, with a formulation of the problem in research is how to improve students activity and learning outcome in natural science subject by using experiment method. The research used classroom action research which does to students in the fourth grade with a qualitative approach. Data in this research based on an interview, test, and documentation. The result shows that can increase student activity and learning outcome in a natural science subject. Student activity level in cycle 1 33,4% and in cycle II goes up to 75%. While the average score of students in science lessons also increased. In the first cycle, the average score of students is 69.5 or 50%, while in cycle II rose to 80.08 or 83.3%. From the data, it can be concluded that the use of experimental methods in science class IV lessons can improve student activity and learning outcomes. This research can become a recommendation for teachers, that the experimental method can be used as an alternative to innovate learning in the classroom, especially to improve student learning outcome.